Negotiating Muslim Women’s Rights and Identity in American Diaspora Space: An Islamic Feminist Study of Kahf’s The Girl in the Tangerine Scarf (KEMANUSIAAN The Asian Journal of Humanities, 2018)
This paper addresses the narrative of a Muslim woman who struggles to negotiate her rights, identity and sense of belonging in an American diaspora space. Despite the difficulties and obstacles of being regarded as an “other” in her adopted homeland, Khadra Shamy, the protagonist in Mohja Kahf’s The Girl in the Tangerine Scarf, chooses to maintain her Islamic identity with a new interpretation of her faith while attempting to build a hybrid identity as an American Muslim. The narrative implies that not all Muslims interpret their religion in the same way and that Muslims identify themselves with Islam to differing degrees. Hence, the media and critics of Islam clearly distort social reality when they depict all Muslims as extremists and all Muslim women as abject individuals. In addition, the employment of Islamic feminism in the analysis of the novel is an approach that can help enhance our knowledge concerning problems connected to the patriarchy that are pertinent in many Muslim communities, including ones in the West. The diaspora space in America has become a platform for Muslim women to gain more freedom, particularly the freedom to negotiate their rights and identities and to reinterpret religious teachings in a new light, a freedom that they may not be able to achieve in some Muslim-majority countries.